The effect of sacral nerve stimulation on distal colonic motility in patients with faecal incontinence (Br J Surg 2013; 100: 959–968). Issue 10 (12th August 2013) - Smart, N.
Abstract : The Editors welcome topical correspondence from readers relating to articles published in the Journal. Responses should be sent electronically via the BJS website (www.bjs.co.uk). All letters will be reviewed and, if approved, appear on the website. A selection of these will be edited and published in the Journal. Letters must be no more than 250 words in length.